2016
DOI: 10.1093/cercor/bhw066
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity-Related Gene 1 Affects Mouse Barrel Cortex Function via Strengthening of Glutamatergic Thalamocortical Transmission

Abstract: Plasticity-related gene-1 (PRG-1) is a brain-specific protein that modulates glutamatergic synaptic transmission. Here we investigated the functional role of PRG-1 in adolescent and adult mouse barrel cortex both in vitro and in vivo. Compared with wild-type (WT) animals, PRG-1-deficient (KO) mice showed specific behavioral deficits in tests assessing sensorimotor integration and whisker-based sensory discrimination as shown in the beam balance/walking test and sandpaper tactile discrimination test, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Spine density could be recovered by interfering with a signaling pathway by which a specific intracellular PRG-1 domain, via direct interaction with PPP2R2A, resulted in activation of ITGB1. This PRG-1 action is independent of its known extracellular role in controlling LPA receptor-mediated synaptic hyperexcitability (Trimbuch et al, 2009;Unichenko et al, 2016), and essential for proper spatial memory. These data provide evidence for the fact that PRG-1 controls hippocampal synaptic plasticity that is important for related memory function in a cell-autonomous fashion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Spine density could be recovered by interfering with a signaling pathway by which a specific intracellular PRG-1 domain, via direct interaction with PPP2R2A, resulted in activation of ITGB1. This PRG-1 action is independent of its known extracellular role in controlling LPA receptor-mediated synaptic hyperexcitability (Trimbuch et al, 2009;Unichenko et al, 2016), and essential for proper spatial memory. These data provide evidence for the fact that PRG-1 controls hippocampal synaptic plasticity that is important for related memory function in a cell-autonomous fashion.…”
Section: Discussionmentioning
confidence: 96%
“…Since spine density can be affected by neuronal activity (McKinney et al, 1999), we have addressed a role of altered neuronal activity observed in PRG-1-deficient animals (Trimbuch et al, 2009) on spine density. The non-cell-autonomous PRG-1 role in controlling excitability results in an increase in synaptic strength of PRG-1 À/À animals (Trimbuch et al, 2009;Unichenko et al, 2016) and requires the presence of presynaptic LPA 2 receptor signaling (Trimbuch et al, 2009), and this hyperexcitability was fully reversed in LPA 2 receptor (LPA 2 R)/PRG-1 double-deficient animals (Trimbuch et al, 2009). Hence, we tested for the possibility that alteration in spine densities can be explained by the LPA 2 R-mediated non-cell-autonomous effect of PRG-1 on neural excitability and analyzed spine density in PRG-1-deficient animals on an LPA 2 R À/À background ( Figure 5J).…”
Section: Prg-1 Regulates Spine Plasticity and Spatial Memory In Cell-mentioning
confidence: 99%
“…The Prg1 -/mice who survived their spontaneous status epilepticus lived on normally after P22 (verified by video monitoring), when seizures spontaneously ceased (Trimbuch et al, 2009). (ii) Prg1 is expressed in the mouse hippocampus during postnatal brain development (Bräuer et al, 2003;Unichenko et al, 2016), and (iii) the EEG of the Prg1 -/animals showed prominent irregular high-amplitude, slow-frequency discharges, multifocal spikes, and absent topical organization reminiscent of hypsarrhythmia, a hallmark of West syndrome (Dulac, 2001). We thus chose a cohort of 18 children with idiopathic West syndrome (infantile spasms).…”
Section: Discussionmentioning
confidence: 99%
“…The PRG1 protein is expressed at the postsynaptic density of glutamatergic synapses (Bräuer et al, 2003) in several brain regions, including the hippocampus and the somatosensory cortex (Trimbuch et al, 2009;Unichenko et al, 2016). Together with the astrocytic enzyme autotaxin (ATX), PRG1 regulates the presynaptic release probability via transmission-dependent changes in the concentration of the lipid messenger molecule LPA in the synaptic cleft (Yung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Humans with PRG1 impairments show altered sensory integration (Vogt et al, 2016). In mice with an equivalent of the human mutation of PRG1, the dysfunction of the PRG1 mechanism produces pathologically high presynaptic release probabilities (Trimbuch et al, 2009) and impaired short-term synaptic plasticity in glutamatergic synapses (Unichenko et al, 2016). At the network level, this produces an overall shift of the excitation-inhibition balance towards excitation, facilitating hyperexcitability (Trimbuch et al, 2009) and changes in both the spontaneous and the evoked activity of neuronal networks (Unichenko et al, 2016;Vogt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%